Analysis of the Influence of Pedagogic and Professional Competencies on the Performance of Islamic Religious Education Teachers in MTs in West Mendo - Dewi, Ratna; Rahman, Priyanggo Karunia (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to analyze the influence of pedagogical competence and professional competence on the performance of Islamic Religious Education (PAI) teachers at MTs in Mendo Barat District. The research uses a descriptive quantitative approach, with a population consisting of all 35 Islamic Education teachers in the area. Data were collected through questionnaires and documentation, and analyzed using descriptive and inferential statistics, including multiple linear regression, t-tests, and F-tests. The results show that, partially, professional competence has a significant effect on teacher performance, as indicated by a significance value of 0.001 (< 0.05). On the other hand, pedagogical competence does not show a significant partial effect, with a significance value of 0.063 (> 0.05). However, when tested simultaneously, both types of competence have a significant influence on teacher performance, contributing 64.6% to the performance variation, as reflected by the adjusted R² value. These findings indicate that improving teacher performance in Islamic Religious Education requires not just one type of competence, but a balanced integration of both. Therefore, enhancing both professional and pedagogical competencies in a complementary manner is crucial in supporting the quality of Islamic education in schools